Implementation of the Information-Motivation-Behavior Skills Model in Child Development: A Path Analysis - Diani Fadmi Putri; Eti Poncorini Pamungkasari; Bhisma Murti (Journal of Epidemiology and Public Health, 2024)
Background: Child development problems also still occur in DI Yogyakarta. Children's development is influenced by parents in educating and nurturing children. Many factors affect maternal parenting patterns including knowledge, attitudes, motivation and skills. The purpose of the study was to analyze the contextual influence of maternal parenting behavior on the development of children under five in Sleman Regency.Subjects and Method: This study uses a cross-sectional design. The research was conducted in 25 Integrated Health Posts with a total of 200 research subjects for mothers of toddlers and children under five. The sampling techniques are stratified random sampling and simple random sampling. The independent variables in this study were information, motivation, skills/skills of child development, parenting behavior, and maternal age, while the dependent variable was the development of children under five. Data collection was carried out using a questionnaire and analyzed by path analysis.Results: Every 1 unit increase in parenting behavior (b= 0.60; CI 95%= 0.44 to 0.76; p< 0.001), skills/skills of child development through parenting behavior (b= 0.44; CI 95%= 0.33 to 0.56; p<0.001), information through parenting behavior (b=0.20; CI 95%= -.074 to 0.32; p= 0.002), motivation through parenting behavior (b= 0.18; CI 95%= 0.06 to 0.30; p= 0.003), and maternal age through parenting behavior (b= 0.05; CI 95%= -0.05; CI 95%= -0.05 to 0.15, p= 0.323) will be followed by an improvement in child development.Conclusion: The Information, Motivation, and Behavior skill model can be used to explain parenting behavior and child development. Children's development increases with good parenting behavior. Parenting behavior is influenced by children's developmental skills/skills influenced by the presence of information and motivation.